Unrevealing Energy Dissipation During Iron Ore Transfer Through Chutes with Different Designs - Jacobs-Capdeville, P (Elsevier B.V., 2024)
This paper comprehensively analyzes the transportation of iron-bearing solid materials in industrial-scale transfer chute stations by a GPU-DEM model. It considers five chute head designs, including the traditional rock box, impact plate, and hood, as well as the modified micro-boxed alternatives to the impact plate and hood. Particle flow and energy dissipation are analyzed to understand the energy consumption, wall wear, and particle degradation and segregation. The numerical results show that the localizations of different energy dissipation mechanisms significantly differ, resulting in differences in particle degradation and segregation across the chutes considered. The rock box chute is susceptible to the largest degradation and segregation. The micro-box impact plate leads to the least degradation, and the traditional hood causes the best mixing performance. It also shows that segregation becomes more severe as the particle flow stream loses greater energy at the earlier stage of the particle dropping. © 2024 The Authors
Keywords: Transfer chute; GPU-DEM; Energy dissipation; Wear; Degradation; Segregation